Incidence and Factors Associated with Postpartum Perineal Pain in Primipara - Jetana Watanatitan; Sornpin Armarttasn; Sumonmal Manusirivithaya (The Royal Thai College of Obstetricians and Gynaecologists, 2009)
Objectives: To determine the incidence and factors associated with postpartum perineal pain after vaginal delivery in primiparous women. Study design: Prospective descriptive study. Subjects: Primipara with episiotomy following vaginal delivery at Bangkok Metropolitan Administration Medical College and Vajira Hospital during August 2008 to September 2008. Methods: Two hundred and ninety nine primiparous women were recruited for this study. General data of the included subjects were collected from medical records and the pain score was assessed with an 11-point verbal analogue scale within 48 hours after delivery. Results: The incidence of significant postpartum perineal pain (pain score more than 3) was 41.1% on the first day of postpartum. And only 8.7% associated with perineal pain at the same level on day two. Factors associated with this pain were operative vaginal delivery and duration of second stage (> 30 minutes). But no statistical difference between maternal BMI, neonatal birth weight, degree of perineal trauma, suturing technique or suture material on perineal pain score. Conclusion: Postpartum perineal pain is common among primiparous women especially in the initial day. Perineal pain was more severe with operative vaginal delivery and duration of second stage more than 30 minutes.